Modern small industry for developing countries - Staley, Eugene; Morse, Richard (New York : McGraw-Hill Book Company, 1965)
The authors offer a comprehensive study of the role of small industry in several economies together with a wealth of examples of small industry development programmes largely drawn from material produced by a research programme carried on at the Stanford Research Institute. On the basis of this material, which occupies the greater part of the book, they develop some conclusions about the role of small industry in developing economies and a general framework for the creation of a small industry development programme which can be particularized to suit the requirements of a specific economy.
Includes bibliographical references and index.
lje 20/4/18
Loans
Keywords: Small business; Developing countries; Economic conditions; Industries